Rabies: Diagnostic, Treatment, and Prevention - Bintang, Andi Kurnia; Basri, Muhammad Iqbal; Lotisna, Mimi; Carrey, Michael (Nusantara Medical Science Journal, 2023)
Rabies is a neurological disease with fatal impacts because it has a high mortality rate. Animals, primarily dogs, mediate the spread of rabies. Clinical findings of rabies are divided into two categories: classic rabies (furious type) and paralytic type. Furious rabies has many cardinal features, such as fluctuating consciousness, aerophobia or hydrophobia, inspiratory spasm, and autonomic dysfunction. Ascending paralysis with a lower motor neuron lesion is the initial sign of paralytic rabies. The rabies virus invades and lives in neurons. It is virulent. Besides clinical findings, the diagnostic approach can involve radiology, microbiology, and histopathology. There are not only symptomatic treatments for rabies patients but also vaccines, immunoglobulin, and antivirals to decrease the progressivity of the disease. Vaccination programs and animal control have become essential in reducing rabies cases in Indonesia.